Solomon Islands : Operational Procurement Review - World Bank (Washington, DC, 2012)
Solomon Islands is a remote, scattered archipelago about 1,900 km northeast of Australia in the South Pacific, with terrain ranging from about 1,000 mountainous islands to low-lying coral atolls stretching in a 1,450 km chain east of Papua New Guinea across the Coral Sea to Vanuatu. The archipelago covers a total area of 725,197 sq km (approx 280,000 sq miles) with the main islands being Choiseul, New Georgia, Santa Isabel, Guadalcanal, Malaita, and Makira. The Solomon Islands are situated among one of the world's most disaster-prone geographic regions in what is known as the circum-pacific belt, earthquake belt or ring of fire. The low-lying coastal regions of the Solomon Islands can also be subject to damage from tsunamis. In addition, the zone in which the Solomon Islands archipelago is located is an area where cyclones are formed. The Solomon Islands is thus subject to many natural Threats, earthquakes, tsunamis, volcanic eruptions, tropical cyclones and windstorms, floods, landslides, and droughts. The objective of this report is to review the Solomon Islands existing national legislation, policies, procedures, practices, institutional arrangements and organizational capacity for public sector procurement to assess both their acceptability for use in national competitive bidding under World Bank-financed projects and, in the process, provide a benchmarking analysis in key thematic areas.